2019
DOI: 10.1007/s11419-019-00473-2
|View full text |Cite
|
Sign up to set email alerts
|

Suicidal deaths due to helium inhalation

Abstract: Purpose The authors reviewed the literature paying attention to helium suicide rates, autopsy findings in people exposed to helium, methods of collecting biological material for toxicological tests, and analytical methods used for detection and quantification of helium in the collected specimens. Methods All reviewed information was gathered through a detailed search of Scopus, PubMed and the WorldWide Web using relevant keywords, e.g., helium, asphyxia, and suicide. Results The use of helium for suicidal purp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 41 publications
0
4
0
Order By: Relevance
“…In line with previous research, we found SRIU was associated with patients dying by gas inhalation and self-poisoning. 22 , 23 Whilst deaths by carbon monoxide poisoning have been steadily declining in the last few decades, the incidence of poisoning with other gasses is on the rise. 22 SRIU may potentially influence this increase by facilitating both the purchase of these means and instructions for their use.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In line with previous research, we found SRIU was associated with patients dying by gas inhalation and self-poisoning. 22 , 23 Whilst deaths by carbon monoxide poisoning have been steadily declining in the last few decades, the incidence of poisoning with other gasses is on the rise. 22 SRIU may potentially influence this increase by facilitating both the purchase of these means and instructions for their use.…”
Section: Discussionmentioning
confidence: 99%
“… 22 , 23 Whilst deaths by carbon monoxide poisoning have been steadily declining in the last few decades, the incidence of poisoning with other gasses is on the rise. 22 SRIU may potentially influence this increase by facilitating both the purchase of these means and instructions for their use. This has also been reported for suicide by self-poisoning, especially with less commonly used substances.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The wide availability of high-pressure helium tanks from retail stores and the encouragement of “helium huffing” on social media raise concern that helium-related CAGE may be more common than reports suggest. This mechanism should be distinguished from helium-induced asphyxia caused by continuously breathing helium under low pressure [ 17 , 18 ], usually in an attempt at suicide, but occasionally by accident in the pediatric population [ 19 , 20 ].…”
Section: Discussionmentioning
confidence: 99%